2020
DOI: 10.3988/jcn.2020.16.4.674
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus for Treating Orbital and Cranial Form of Idiopathic Inflammatory Pseudotumors

Abstract: Background and Purpose Orbital and cranial form of idiopathic inflammatory pseudotumors (IIPs) are rare disorders with heterogeneous clinical presentations. Corticosteroids have been the first-line treatment for IIPs, but they are not always effective. Methods We reviewed the medical records of three patients with orbital or cranial form of IIP who were treated with tacrolimus as an adjuvant treatment. Results The three patients showed favorable outcomes with the addition of tacrolimus, which is a calcineurin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The might side effects are hypertension, neurotoxicity, diabetes, and nephrotoxicity [ 103 106 ]. Hyun Jae Kim et al reported that tacrolimus may be a secure and efficient immunosuppressant for the treatment of refractory or relapsed OIP [ 107 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The might side effects are hypertension, neurotoxicity, diabetes, and nephrotoxicity [ 103 106 ]. Hyun Jae Kim et al reported that tacrolimus may be a secure and efficient immunosuppressant for the treatment of refractory or relapsed OIP [ 107 ].…”
Section: Treatmentmentioning
confidence: 99%